The Continuity of Matrilineal Systems Within a Market Economy - Yonariza, . (Kasarinlan: Philippine Journal of Third World Studies; Vol 13 No 3 (1998): Social Forces and Communities in Southeast Asia, 2007)
The disintegration of matrilineal societies in the last century has been closely linked to their integration into the market economy. This trend suggests that matrilineal systems or the lineage system organized through the female line will soon vanish as subsistence economies yield to expanding markets. The new prosperity generated by market-oriented production allows the men to become equal members of the women-centered society. Gender roles and rights in matrilineal societies are altered and ultimately this way of life is abolished. The case of Silayang, Minangkabau in West Sumatra provides an exception. Its matrilineal society has persisted despite the dominant presence of Islam, a pillar of patriarchy; the Dutch occupation; and its departure from pure subsistence agriculture via rubber export. Silayang is proof that a matrilineal system will not only survive but also thrive within a market economy, and that economic change does not necessarily bring about social disintegration.